Improvıng Scıence Lıteracy Usıng The Learnıng Cycle 7e Learnıng Model - Safitri, Mazda Leva Okta; Fathurohman, Apit; Nurlaila (Jurnal Elementaria Edukasia, 2024)
The purpose of this study was to improve scientific literacy by using the learning cycle 7e learning model at SDN 148 Palembang because based on the initial test results showed that 70% of 22 students' scientific literacy levels were in the low category, while based on the results of initial observations showed that learning applied in class only used discussion and assignment learning methods. This study uses a type of Collaborative PTK research with the subjects of this study being 22 students in grade 5 (five). This study collaborated with grade V teachers. This study was carried out in 2 cycles with stages, namely planning, action, observation, and reflection. The results of this study show an increase in the average results of participants' scientific literacy in the three indicators of scientific literacy, namely identifying scientific issues, explaining scientific phenomena, and using scientific evidence. The average results of scientific literacy scores on the three indicators in the pre-cycle reached 39%, in cycle I increased to 74.5%, and in cycle II reaching 88%. In cycle II, the results of students' scientific literacy scores met the research performance indicators, namely reaching >75% so the research was stopped in cycle II. So this study shows an increase in Scientific Literacy using the 7E learning cycle model at SDN 148 Palembang.